Pengaruh Kecakapan Manajerial Dan Kinerja Keuangan Terhadap Manajemen Laba - Istiqomah Istiqomah; Vita Elisa Fitriana (JRAK: Journal of Accounting Research and Computerized Accounting, 2018)
The purpose of the study was to examine the effect of the relationship of managerial skills and financial performance on earnings management. Sample from this study is a manufacturing company listed on the Indonesia Stock Exchange (IDX) in 2014 to 2016, and as many as 137 sample companies. Managerial skills are measured using Data Envelopment Analysis (DEA). Financial performance is measured using ROE (Return on Equity) financial ratios. While earnings management is measured by calculating discretionary accruals of modified Jones models. By using multiple regression analysis, it was found that managerial skills did not affect earnings management. Because capable managers tend not to do earnings management. Furthermore, financial performance has a positive effect on earnings management. Because when a company's performance is bad, management tends to maintain the company's reputation for not doing earnings management.